Intricate Analysis of Potential Materials for Sustainable Product Development - Kumar, Sachin; Goel, Anchit; Kumar Singh, Gaurav (European Journal of Sustainable Development, 2019)
Raw materials are scarce and are exponentially depleting. Material usage and product disposal both lead to improvidence of raw ingredients for products. We use materials for manufacturing new products while simultaneously throwing away used non-biodegradable products which pollute the environment. The world of designing and manufacturing needs to use new material(s) which can be selected using the methodology proposed in the research text. To select the best material for a product, its environmental impact, cost and properties that decide the quality of a product are plotted in a 3 dimensional space. Now the threshold limit of quality defining properties is obtained through experimentation. Cutoff cost is decided through market research and then environmental impact is minimized. The material beyond the cutoff planes is rejected and the best among the remaining materials is selected. The product developed using this method for material selection will contain the negative environmental impact during manufacture, use and expenditure of used products and thus helping sustainable development. Keywords: Sustainability, Life Cycle Analysis, Material selection, Cost optimization, Environmental Repercussion, Mechanical properties